Analisis Penerapan Good Corporate Governance (GCG) dan Dampaknya terhadap Penagihan Piutang: (Studi Kualitatif: pada Perumda Air Minum Tirta Hita Buleleng) - Kadek Wimasri Pradnya Iswari; Ni Kadek Sinawati; Nyoman Suadnyana Pasek (AKUNTANSI 45, 2026)
This research is motivated by the high level of uncollectible accounts at PERUMDA Air Minum Tirta Hita Buleleng, which impacts liquidity and public service quality. One of the main contributing factors is the uneven implementation of Good Corporate Governance (GCG) among all employees. This study aims to analyze the implementation of GCG and its impact on debt collection in an effort to minimize uncollectible accounts. The research method used is qualitative with a case study approach. Primary data were obtained through snowball sampling from key informants, including the board of directors and relevant department heads. Data collection was carried out through in-depth interviews, observation, and documentation, which were then analyzed using the Miles and Huberman model (data reduction, data display, and conclusion drawing/verification). The results indicate that the implementation of GCG principles—comprising transparency, accountability, responsibility, independence, as well as fairness and equality—has been carried out well but is not yet fully optimal. The application of these principles has had a significant impact by making the collection process more systematic, structured, and data-driven. This contributes to improving collection effectiveness and arrears control. Nonetheless, challenges remain, such as a lack of customer payment discipline and uneven employee understanding of GCG. The conclusion of this research is that the consistent application of GCG plays a vital role in reducing uncollectible accounts; however, strengthening internal control and continuous education for employees are necessary to achieve maximum corporate financial sustainability.